Sistem Informasi Pendistribusian Obat Berbasis Web Pada Dinas Kesehatan Kabupaten Aceh Singkil - Agustin, Laura; Akbar, Rizaldi; Imilda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This research aims to develop a Web-Based Drug Distribution Information System at the Aceh Singkil District Health Service to overcome challenges in drug management and distribution. The system development method uses a waterfall approach which includes requirements analysis, system analysis, design, development and testing. Data was collected through in-depth interviews and review of related documents. This system is designed to provide fast, accurate and timely information, replacing manual recording and providing reports such as order data and stock items instantly. Web-based, this system was built using PHP with the CodeIgniter framework and MySQL as the database. It is hoped that this research can contribute to the concept of drug distribution management and make it easier for agencies to run the distribution system.